Phosphonium-Based Polyelectrolytes: Preparation, Properties, and Usage in Lithium-Ion Batteries - Misenan, Muhammad Syukri Mohamad; Hempelmann, Rolf; Gallei, Markus; Eren, Tarik (MDPI, 2023)
Phosphorous is an essential element for the life of organisms, and phosphorus-based compounds have many uses in industry, such as flame retardancy reagents, ingredients in fertilizers, pyrotechnics, etc. Ionic liquids are salts with melting points lower than the boiling point of water. The term polymerized ionic liquids (PILs) refers to a class of polyelectrolytes that contain an ionic liquid (IL) species in each monomer repeating unit and are connected by a polymeric backbone to form macromolecular structures. PILs provide a new class of polymeric materials by combining some of the distinctive qualities of ILs in the polymer chain. Ionic liquids have been identified as attractive prospects for a variety of applications due to the high stability (thermal, chemical, and electrochemical) and high mobility of their ions, but their practical applicability is constrained because they lack the benefits of both liquids and solids, suffering from both leakage issues and excessive viscosity. PILs are garnering for developing non-volatile and non-flammable solid electrolytes. In this paper, we provide a brief review of phosphonium-based PILs, including their synthesis route, properties, advantages and drawbacks, and the comparison between nitrogen-based and phosphonium-based PILs. As phosphonium PILs can be used as polymer electrolytes in lithium-ion battery (LIB) applications, the conductivity and the thermo-mechanical properties are the most important features for this polymer electrolyte system. The chemical structure of phosphonium-based PILs that was reported in previous literature has been reviewed and summarized in this article. Generally, the phosphonium PILs that have more flexible backbones exhibit better conductivity values compared to the PILs that consist of a rigid backbone. At the end of this section, future directions for research regarding PILs are discussed, including the use of recyclable phosphorus from waste.
Keywords: polymeric ionic liquid; phosphonium; polymer electrolyte; energy storage; lithium-ion batteries; LIFE-CYCLE ASSESSMENT; GAS-TRANSPORT PROPERTIES; POLYMER ELECTROLYTES; POLY(ETHYLENE OXIDE); GEL ELECTROLYTE; WASTE-WATER; LIQUIDS; CONDUCTIVITY; COPOLYMERS; MEMBRANES; Polymer Science